Dyslipidemia’s influence on the secretion ovarian’s steroids in female mice (Research, Society and Development, 2021)
Introduction: The synthesis ovarian’s steroids is a process thats depends on the supply of cholesterol. Objective: to evaluate the influence of dyslipidemia on the secretion ovarian’s steroids. Methodology: wild female mice were used (C57BL6) and LDL (LDLR-/-), which they were separated into 4 groups (n = 10): WTS: fed a standard diet; WTHL: fed a high-fat diet; KOS: fed a standard diet; KOHL: fed a high-fat diet. After 60 days, the estrous cycle was analyzed and after anesthetized, blood was collected for the to assess the lipid profile, glucose, plasma insulin level and HOMA index was calculated. In addition, plasma levels of C-reactive protein, estrogen and progesterone were determined. Results: The hyperlipidic diet in both the WTHL and the KOHL group generated hypercholesterolemia when compared to the WTS and KOS, respectively, with a decrease in HDLc, associated with an increase in CRP levels. Severe hypercholesterolemia in the KOHL group generated insulin resistance, marked by an increase in HOMAir. Food hypercholesterolemia in the WTHL group, food and genetics in the KOHL group, compared to their WTS and KOS controls, was definitive in reducing plasma levels of estrogen and progesterone. The genetic hypercholesterolemia associated with insulin resistance observed in the KOS and KOHL groups reduced the levels of progesterone, this reduction being more severe in the KOHL group, which had the highest HOMAir. Conclusion: dyslipidemia affected ovarian steroidogenesis in mice by means of oxidative stress, inflammation and insulin resistance and / or by decreasing HDL cholesterol levels.